Manejo de lepidópteros en Vaccinium corymbosum L. en Santa Elena y Víctor Raúl en Virú, La Libertad - Neira Chavez, Angélica Martina (2019)
This research work was carried out in the area of Víctor Raúl and Santa Elena La Libertad with the aim of describing the management of Lepidoptera in Vaccinium corymbosum L. in Santa Elena and Víctor Raúl in Virú, La Libertad, the methodology was descriptive, the Information was obtained through visits and personalized interviews, complemented with a survey of the people responsible for the area of agricultural health, the study was based on two phases, the first phase, a baseline was established according to aspects technicians such as knowledge of agroecosystems and cultivation, knowledge about Lepidoptera and in the second phase, information was collected through interviews and surveys based on the results obtained at baseline, a management of Lepidoptera was established in Vaccinium corymbosum L. concludes that the management of Lepidoptera includes cultural control methods such as; weed removal, application of organic matter in the installation, proper management of fertilization and irrigation, constant evaluation of the population dynamics of Lepidoptera; biological control methods; use of biological agents Bacillus thuringiensis at a dose of 0.5 kg / ha and nuclear polyhedrosis virus at a dose of 0.4 L/200L; ethological control, to monitor adults of Lepidoptera through the use of black traps, light traps, molasses; Chemical control method such as the use of insecticides with active ingredients, Spinosad, spinetoram, Chlorantraniliprole.